Review of Islamic Law on Customary Law Values in Community in North Lore Utara And Lore Peore, Poso-Indonesia - MS, Syaifullah; Cikka, Hairuddin (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
Long before state law, customary law was in effect, and no ordinary or customary law itself taught deviant behavior. Customs correct the wrong and provide solutions to social problems. The custom in the Pekurehua area is called the Pekurehua Tawailia custom, which is divided into the four largest divisions, namely the Posamboko custom/marriage, the mpogalo galo custom, or social order, the mpowia custom or farming methods, and the ngkapate custom or death. The objective of this research is to analyze the Islamic Law on Customary Law Values in Community in North Lore Utara And Lore Peore, Poso-Indonesia. the method used by this research is Empirical juridical. The collecting data method is by the interview. The result of this research is the implementation of customary law values in North Lore and Lore Peore Districts, Poso District, is deeply ingrained in the region's historical, cultural, and religious contexts and The implementation of customary law values in the Napu Valley or Pekurehua region of Poso Regency is a complex interplay between historical traditions, cultural practices, and Islamic teachings Keyword : Islamic Law; Customary Law; Poso Indonesia.